MORPHOLOGICAL CHANGES IN THE VASCULAR LAYER OF EYEBALL UNDER THE EFFECT OF NARCOTIC ANALGETICS (EXPERIMENTAL STUDY) - Pidvalna, U.Ye.; Dzhura, O.R.; Mateshut-Vatseba, L.R. (World of Medicine and Biology, 2017)
Dynamic increase in the number of people who have to use narcotic analgesics for the long periods of time has led to the higher incidence of narcological diseases in Ukraine, that has affected about one million people. Analysis of professional literature shows the importance of research pertaining to this problem. Taking into account rareness of the works dealing with the effect of narcotic analgesics on the structure of the eyeball, our objective was to determine peculiarities of the vascular layer of eyeball structure under the effect of 6-weeks long application of opioid (Nalbuphine) in the experiment. The studies were performed on 24 mature white male rats. The study material was presented by the histologic specimens of the white rats’ vascular layer of eyeball. Histologic sections were stained with hematoxylin-eosin. Modeling of the prolonged effect of the opioid was made using semisynthetic opioid analgesic of agonist-antagonist group of opiate receptors Nalbuphine hydrochlorine. Injection was made every day intramuscularly in gluteal region at the same time. Euthanasia was made using the method of overdosing intraperitoneal anesthesia using thiopental sodium. All experimental procedures were approved by the University Animal Care and Use Bioethical Committee. The animals were kept under standard vivarium of conditions. After 6 weeks of injecting Nalbuphine to the rats there are observed deep destructive changes in the eyeball vascular tunic. The number of fibroblasts and collagen fibers in connective tissue base of choroid grows. Arterioles’ walls are thickened due to sclerosis. Thin-walled, elongated venules prevail. Choriocapillar layer is destroyed. The number of capillaries is smaller. Sometimes the capillaries’ walls are damaged and there are outflows of blood outside the vessels. Characteristic is the pronounced perivascular swelling. Deep changes were also found in the ciliary body. Ciliary processes are fragmented, epithelium that covers them is disorganized, the processes are thickened, shortened. Venules are dramatically dilated, have irregular contours. Arterioles are tortuous, their walls sclerotized, thickened, aggregation of erythrocytes, adhesion is noted in most of them. Layers of the iris are not clearly differentiated. Venules of the iris are also dilated. There are observed aneurysmal dilatation of arterioles, parietal thrombi in microvessels. There is also a considerable swelling around the vessels. After 6 weeks of injecting Nalbuphine to the rats both, hemomicrovasculature and the connective tissue matrix are affected of the choroid. There is no differentiation of the iris layers and fragmentation of ciliary processes. The identified changes in the iris, ciliary body and the choroid are of a destructive nature.